2016
DOI: 10.1002/tcr.201500298
|View full text |Cite
|
Sign up to set email alerts
|

Optically Active Hybrid Materials Constructed from Helically Substituted Polyacetylenes

Abstract: Functional materials derived from synthetic helical polymers are attracting increasing interest. Helically substituted polyacetylenes (HSPAs) are especially interesting as typical artificial helical polymers. In recent years, we designed and prepared a series of functional materials based on HSPAs and inorganic materials. The target is to establish some novel hybrid materials that combine the superior properties of both. The examined inorganic materials include silica, graphene, and magnetic Fe3 O4 nanoparticl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 85 publications
(72 reference statements)
0
4
0
Order By: Relevance
“…[18] The Deng, Jianping group has been very active in preparation and application of chiral polymeric and chiral inorganic-polymeric hybrid nanoparticles based on optically active helical polymers. [30][31][32][33][34][35][36][37][38][39] Further research in the area of chiral polymeric nanomaterials was conducted by O'Reilly and coworkers who developed new methods for synthesis of chiral micelles and nanoparticles for applications in organocatalysis. [40][41][42][43] In addition to this field advanced chiral polymers have been synthesized with grafted optically active helical polymeric structures and has been applied to chiral recognition.…”
Section: Doi: 101002/macp202000328mentioning
confidence: 99%
“…[18] The Deng, Jianping group has been very active in preparation and application of chiral polymeric and chiral inorganic-polymeric hybrid nanoparticles based on optically active helical polymers. [30][31][32][33][34][35][36][37][38][39] Further research in the area of chiral polymeric nanomaterials was conducted by O'Reilly and coworkers who developed new methods for synthesis of chiral micelles and nanoparticles for applications in organocatalysis. [40][41][42][43] In addition to this field advanced chiral polymers have been synthesized with grafted optically active helical polymeric structures and has been applied to chiral recognition.…”
Section: Doi: 101002/macp202000328mentioning
confidence: 99%
“…Deng and coworkers managed to form hybrid organic and inorganic CPPs based on optically active helical polymers. [17][18][19][20][21][22][23][24][25][26] One of the fastest growing elds in chemistry is organocatalysis which are formed by mostly natural products that does not have a metal which in substoichiometric amounts accelerates a reaction. 27 Catalyzed direct asymmetric aldol reaction comprising a nonactivated ketone as a nucleophile is one of the most useful reactions for the formation of C-C chains.…”
Section: Introductionmentioning
confidence: 99%
“…Deng and coworkers managed to form hybrid organic and inorganic CPPs based on optically active helical polymers. 17–26…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the studies accomplished so far have demonstrated that the polymer chains in solid particles can still form helical structures. [20] Chiral polyacetylenic particles can be directly used, and the deficiencies of original polyacetylenes such as poor processibility, low solubility, low stability against heat and oxygen are thus anticipated to be circumvented accordingly. Thereby the progress in CPPs also helpfully promotes the advancements in non-chiral polyacetylenes.…”
Section: Introductionmentioning
confidence: 99%